Dental health and diet in a medieval Muslim population from Southern Spain - López-Morago, Claudia; Estévez, Enrique J; Alemán, Immaculada; Botella, Miguel (Anthropologie, 2020)
The aim of this study was to evaluate the oral health and diet of a Medieval Muslim sample from Granada in southern Spain (11th – 15th centuries), in which the sex and age of the remains had been established. Carious lesions, linear enamel hypoplasia, dental calculus and tooth wear were the pathologies examined in this paper. A total of 961 permanent teeth and 1009 alveoli belonging to sixty individuals (32 males and 28 females) were observed. Adult males exhibited significantly higher prevalence of tooth wear, while females exhibited higher prevalence of caries and dental calculus. The highest frequency of linear enamel hypoplasia was determined in juvenile individuals. Additionally, a peak age at stress of 2.5 to 3 years was recorded in the sample. This paper showed that frequency and distribution of dental pathologies in the Medieval population of Granada is very similar to that other agricultural European populations of the same socio-economic status during the same historic period. The level of caries and dental calculus could be associated with a carbohydrate-rich diet with only occasional consumption of meat. Furthermore, significant differences between adult men and women in the sample studied suggest different nutritional patterns during adulthood with females consuming food mostly based on carbohydrates in comparison to males.
Keywords: hypoplazie zubní skloviny; Španělsko; Statistics as Topic; zubní kaz; Female; islám; Spain; statistika jako téma; Age Factors; opotřebení zubů; ženské pohlaví; Tooth; Tooth Diseases; History, Medieval; stravovací zvyklosti; věkové faktory; lidé; Dental Caries; zubní kámen; Tooth Wear; Epidemiologic Studies; Male; Feeding Behavior; zuby; zubní sklovina; dějiny středověku; Islam; epidemiologické faktory; Dental Calculus; epidemiologické studie; nemoci zubů; mužské pohlaví; Dental Enamel; Epidemiologic Factors; Dental Enamel Hypoplasia; Humans